2020
DOI: 10.1001/jamaoto.2020.1018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Therapeutic Positive Airway Pressure as a Hypoglossal Nerve Stimulation Predictor in Patients With Obstructive Sleep Apnea

Abstract: bstructive sleep apnea (OSA) is a disorder that involves complete or partial blockage in airflow during sleep. The resulting hypoxia and sympathetic activation place patients at an increased risk for metabolic syndrome, neurocognitive decline, hypertension, stroke, and other cardiovascular sequelae. 1,2 The primary therapy for OSA is positive airway pressure (PAP); however, although PAP treatment is beneficial, recommended adherence to therapy ranges from 17% to 54%. 3 Consequently, there exists a need for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Additionally, neck circumference, age, and sex are also unreliable predictors of response [ 6 ]. A more consistent finding is that lower pre-operative and intra-operative PAP required for airway opening [ 11 , 12 ] is associated with a greater reduction in the AHI with HGNS. The association of lower airway opening pressures with HGNS efficacy suggests that responders have more compliant airways, particularly at the level of the soft palate, which may be more amenable to airway opening with HGNS.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, neck circumference, age, and sex are also unreliable predictors of response [ 6 ]. A more consistent finding is that lower pre-operative and intra-operative PAP required for airway opening [ 11 , 12 ] is associated with a greater reduction in the AHI with HGNS. The association of lower airway opening pressures with HGNS efficacy suggests that responders have more compliant airways, particularly at the level of the soft palate, which may be more amenable to airway opening with HGNS.…”
Section: Introductionmentioning
confidence: 94%
“…As our preliminary data using quantification of physiology during DISE have shown predictive capacity in HGNS-related outcomes [23], we continue to expand our resources into the physiologic assessment during DISE.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In order to do so, we identified a DISE outcome measure (PhOP) analogous to the minimally effective therapeutic PAP level obtained from natural sleep. In 2019, we conducted a DISE study which demonstrated the ability of a single, objective measurement – POP (DISE-POP) – to predict outcomes for HGNS beyond that of both the VOTE score and commonly used anthropometric measures [23]. Subsequently, our group formally launched a specialized protocol: Drug-Induced Sleep Endoscopy-Characterization of Airway Dynamics (DISE-CAD).…”
Section: Drug-induced Sleep Endoscopy – Characterization Of Airway Dy...mentioning
confidence: 99%
“…Patients with CHF often present with obstructive sleep apnea syndrome (OSAS) [54]. We know that one of the main causes of OSAS is morphological and functional alterations of the tongue, in particular, an increase in posterior volume and an alteration of the intervention of the autonomic nervous system [55,56]. Lingual dysfunction in CHF and OSAS raises the likelihood of systemic metabolic disorders, with the risk of further cardiovascular sequelae, the onset of metabolic syndrome, and cognitive impairment [56].…”
Section: Mri: Magnetic Resonance Imagingmentioning
confidence: 99%